Employment inequality according to disability status in turkey: Gender differences - DÜZGÜN ÖNCEL, BURCU (My University, 2022)
Females consistently participate in the labor force less than males in Turkey. This holds true for individuals with and without disabilities in different education groups. This study explores the difference in labor market outcomes of males and females with disabilities across education groups. By using World Health Organization’s definition of disability and TURKSTAT Health Survey 2019, I decompose how much of employment inequality by education can be attributed to disparities in disability status among genders. The results present that probability of being out of labor force is higher for disabled individuals both for males and females and this probability decreases with education. Decomposition results also show that probability of employment is lower for individuals with severe disabilities in all education groups. The association between education and inequality in employment with respect to disability status is more profound for females.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); employment; disability; education; decomposition